Comprehensive expression analysis of cardiac fibroblast growth factor 23 in health and pressure-induced cardiac hypertrophy - Rohde, Fiona; Richter, Beatrice; Schwänen, Saskia; Szaroszyk, Malgorzata; Vogt, Isabel; Grund, Andrea; Thum, Thomas; Heineke, Jörg; Haffner, Dieter; Leifheit-Nestler, Maren (Frontiers in cell and developmental biology, 2022)
Enhanced fibroblast growth factor 23 (FGF23) is associated with left ventricular hypertrophy (LVH) in patients with chronic kidney and heart disease. Experimentally, FGF23 directly induces cardiac hypertrophy and vice versa cardiac hypertrophy stimulates FGF23. Besides the bone, FGF23 is expressed by cardiac myocytes, whereas its synthesis in other cardiac cell types and its paracrine role in the heart in health and disease is unknown. By co-immunofluorescence staining of heart tissue of wild-type mice, we show that Fgf23 is expressed by cardiac myocytes, fibroblasts and endothelial cells. Cardiac Fgf23 mRNA and protein level increases from neonatal to six months of age, whereas no age-related changes in bone Fgf23 mRNA expression were noted. Cardiac myocyte-specific disruption of Fgf23 using Cre-LoxP system (Fgf23fl/fl/cre+) caused enhanced mortality, but no differences in cardiac function or structure. Although pressure overload-induced cardiac hypertrophy induced by transverse aortic constriction (TAC) resulted in a slightly worse phenotype with a more severe reduced ejection fraction, higher end-systolic volume and more enlarged systolic LV diameter in Fgf23fl/fl/cre+ mice compared to controls, this was not translated to any worse cellular hypertrophy, fibrosis or chamber remodeling. TAC induced Fgf23 mRNA expression in whole cardiac tissue in both genotypes. Interestingly, co-immunofluorescence staining revealed enhanced Fgf23 synthesis in cardiac fibroblasts and endothelial cells but not in cardiac myocytes. RNA sequencing of isolated adult cardiac myocytes, cardiac fibroblasts and endothelial cells confirmed significantly higher Fgf23 transcription in cardiac fibroblasts and endothelial cells after TAC. Our data indicate that Fgf23 is physiologically expressed in various cardiac cell types and that cardiac fibroblasts and endothelial cells might be an important source of FGF23 in pathological conditions. In addition, investigations in Fgf23fl/fl/cre+ mice suggest that cardiac myocyte-derived FGF23 is needed to maintain cardiac function during pressure overload.